Validation and adaptation of the Spanish version of the systemic lupus activity questionnaire (S-SLAQ) in an Argentinean population. (December 2021) - Catoggio, Cecilia; Martínez Muñoz, Alejandro; Chaparro del Moral, Rafael; Klajn, Diana S; Papasidero, Silvia B; Machado Escobar, Maximiliano A; Gonzalez Lucero, Luciana; Lucero, Eleonora; Martinez, Liliana; Muñoz, Sebastian A; Collado, María Victoria; Gomez, Graciela N; et al.
Objectives: To validate the systemic lupus activity questionnaire (SLAQ) in Spanish language. Methods: The SLAQ questionnaire was translated and adapted in Spanish. Consecutive SLE patients from 8 centers in Argentina were included. A rheumatologist completed a Systemic Lupus Activity Measure (SLAM), Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)-2K, and a physician's assessment. Reliability was assessed by internal consistency (Cronbach's alpha), stability by test–retest reliability (intraclass correlation coefficient), and construct validity by evaluating the correlation with clinically relevant scores. Sensitivity and specificity for clinically significant disease activity (SLEDAI ≥6) of different S-SLAQ cut-off points were evaluated. Results: We included 97 patients ((93% female, mean age: 40 years (SD14.7)). Internal consistency was excellent (Cronbach's alpha = 0.84, p < 0.001), and the intraclass correlation coefficient was 0.95 ( p < 0.001). Mean score of S-SLAQ was 8.2 (SD 7.31). Correlation of S-SLAQ was moderate with Patient NRS (r= 0.63 p < 0.001), weak with SLAM-no lab ( r = 0.42, p <0.001) and SLAM ( r = 0.38, p < 0.0001), and very weak with SLEDAI-2K ( r = 0.15, p =0.1394). Using the S-SLAQ cutoff of five points, the sensitivity was 72.2% and specificity was 37.9%, for clinically significant disease activity. Conclusions: The S-SLAQ showed good validity and reliability. A good correlation, similar to the original instrument, was observed with patient´s global disease activity. No correlation was found between S-SLAQ and gold standard disease activity measures like SLEDAI-2K and SLAM. The S-SLAQ cutoff point of 5 showed a good sensitivity to identify the active SLE population and therefore could be an appropriate screening instrument for disease activity in clinical and epidemiological studies.